Signs and symptoms of anxiety and depression in nursing students: integrative literature review - Santo, Maiara Santos do Espirito (2022)
Objective: To identify the evidence available in the scientific literature about the involvement of nursing students in signs and symptoms of anxiety and depression. Methodology: This is an Integrative Literature Review, exploratory with a qualitative approach on the occurrence of signs and symptoms of depression in nursing students, carried out in national and international databases, in the period from 2014 to 2020. Result: The final sample was composed of 8 studies, which present the established criteria. It is noteworthy that the development of signs and symptoms of anxiety and depression in nursing students are increasingly frequent, significantly affecting their quality of life. Conclusion: The theme is still permeated by ignorance and scarcity of adequate research and interventions, therefore, it is necessary to carry out new studies that address the main actions taken to reduce cases and exposure of this population, through adequate support during graduation.